Simulation Analysis and Experimental Research on a Vibration Damping Structure of Cylindrical Spur Gear Slot Holes - Xie Xuekai; Wei Bingyang; Gu Dewan; Liu Kang (Jixie chuandong)
A kind of clearance elimination and vibration reduction structure of cylindrical gear slot holes is proposed. The vibration acceleration of slotted and backlash gears with different sizes is simulated using the dynamics software Adams. The vibration acceleration spectrum and power spectrum are obtained by Fourier transform and correlation power spectrum estimation method. A three-factor and three-level orthogonal test table is designed. Taking the amplitude of angular acceleration of meshing frequency as the evaluation index of orthogonal tests, the relatively optimal parameter design scheme is obtained. The effectiveness of the proposed damping structure design is verified by vibration tests. The slot structure can reduce the gear vibration acceleration by about 20%-33%, and the test results are similar to the simulation results. Under the constraint of slot relaxation, the negative backlash has an obvious inhibitory effect on the vibration.